The World Bank procurement training ([S.l.] : World Bank Publications, 1999)
The program consists two major sections: the Learn Board and the Case Studies
IBM-PC compatible computer with 80486 processor running at 50 MHz or better, Windows 3.1, super VGA (SVGA) display card, monitor, driver, sound card with speakers or headphones, double-speed CD-ROM drive
Keywords: World Bank -- Procurement; Economic development projects -- Finance